2020
DOI: 10.1111/jth.15095
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial JAK2V617F mutation leads to thrombosis, vasculopathy, and cardiomyopathy in a murine model of myeloproliferative neoplasm

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 80 publications
(199 reference statements)
2
21
0
1
Order By: Relevance
“…The possible association of this condition with MPN has not been explored, and any etiological relationship remains unclear. Given the recent evidence that MPN affects vascular endothelial cells and triggers atherosclerosis [22][23][24], we included the condition in the pool of thrombotic vascular events. Unlike our findings regarding thrombotic events, the incidence and pattern of hemorrhagic events were similar to those described in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The possible association of this condition with MPN has not been explored, and any etiological relationship remains unclear. Given the recent evidence that MPN affects vascular endothelial cells and triggers atherosclerosis [22][23][24], we included the condition in the pool of thrombotic vascular events. Unlike our findings regarding thrombotic events, the incidence and pattern of hemorrhagic events were similar to those described in previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Castiglione et al demonstrated that the MPN phenotype in Tie2-Cre/FF1 mice, that express JAK2 V617F in both hematopoietic and ECs is associated with thrombosis, vasculopathy, and cardiomyopathy but that this phenotype is lost if JAK2 V617F expression is restricted only to hematopoietic cells without mutated ECs, suggesting a critical role for mutated ECs in the pro-thrombotic phenotype. Indeed, JAK2 V617F expressing ECs displayed a pro-adhesive, pro-inflammatory, and vasculopathic phenotype [110]. Guy et al…”
Section: Endotheliummentioning
confidence: 99%
“…Endothelial cells (ECs) carrying the JAK2 V617F mutation [108] express a pro-inflammatory transcriptome with increased expression of vWF and P-selectin and increased adhesiveness of leukocytes to ECs [109]. They also display a pro-adhesive, pro-inflammatory, vasculopathic phenotype [110] due to increased endothelial P-selectin exposure, secondary to degranulation of Weibel-Palade bodies. Thrombo-inflammation-Increased levels of pro-inflammatory cytokines such as interleukin (IL)-1β, IL-6, IL-8 and tissue necrosis factor (TNF)-α [112,113], as well as increased inflammatory markers such as C-reactive protein (CRP) and pentraxin-3 [114,115] are found in patients with MPNs.…”
Section: Covid-19 Mpns and Thrombosis-(mechanistic) Lessons Learned From The Pandemicmentioning
confidence: 99%
“…Left ventricular (LV) dimensions at end-systole and end-diastole and fractional shortening (percent change in LV diameter normalized to end-diastole) were measured from the parasternal long-axis view using linear measurements of the LV at the level of the mitral leaflet tips during diastole. LV ejection fraction (EF), volume, and mass are measured and calculated using standard formulas for the evaluation of LV systolic function 32,36 .…”
Section: Transthoracic Echocardiographymentioning
confidence: 99%
“…The mutation can also be detected in 60-80% of EC progenitors derived from the hematopoietic lineage and, in some reports based on in vitro culture assays, in endothelial colony-forming cells from patients with MPNs [22][23][24][25][26] . Previously, we reported that the JAK2V617F-bearing vascular endothelium promotes the expansion of the JAK2V617F mutant HSPCs in preference to wild-type HSPCs [27][28][29][30][31] and contributes to the development of cardiovascular complications 32 in a murine model of MPN. In the present study, we investigated how MPN progresses in the JAK2V617F-bearing vascular niche during aging.…”
Section: Introductionmentioning
confidence: 99%